2006
DOI: 10.1203/01.pdr.0000214991.07965.0f
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Maturation of Third-Trimester Cerebellar Foliation after Birth

Abstract: ABSTRACT:The development of cerebellar folia of third-trimester preterms has not been described with ultrasound before. We set out to determine normal development of the pons and cerebellar folia for future measurements of hypoplasia and atrophy. Study sonograms were made in preterms admitted to the neonatal intensive care unit with postmenstrual age (PMA) from 25 wk until term. On a weekly basis, transcranial measurements were made in the axial and coronal planes at the asterion with high-frequency transducer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Only at age 9 weeks (40 weeks post‐LMP) did a CT scan demonstrate discernible cerebellar hypoplasia. Nomograms for transverse cerebellar diameters during the second trimester have been in clinical use for several decades [Smith, 1986], with a subsequent report of measurements of cerebellar foliation in prematurely born infants at 27 and 34 weeks [Korsten et al, 2006]. Chavez et al 2003 reported a fetal transcerebellar diameter nomogram with special emphasis on the third trimester because the cerebellar structures develop late in gestation making prenatal diagnosis of cerebellar hypoplasia extremely difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Only at age 9 weeks (40 weeks post‐LMP) did a CT scan demonstrate discernible cerebellar hypoplasia. Nomograms for transverse cerebellar diameters during the second trimester have been in clinical use for several decades [Smith, 1986], with a subsequent report of measurements of cerebellar foliation in prematurely born infants at 27 and 34 weeks [Korsten et al, 2006]. Chavez et al 2003 reported a fetal transcerebellar diameter nomogram with special emphasis on the third trimester because the cerebellar structures develop late in gestation making prenatal diagnosis of cerebellar hypoplasia extremely difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Standard imaging was performed through the anterior fontanelle. However, if a lesion in the posterior fossa was suspected, additional imaging was performed at 12–13 MHz through the mastoid fontanelle, also known as the posterolateral fontanelle [8]. Sonograms were obtained using a Sequoia system (Siemens, Mountain View, California), and with Esaote system (Mylab 70, Genova Italy).…”
Section: Methodsmentioning
confidence: 99%